POLEMIK LEMBAGA KOMISI PEMBERANTASAN KORUPSI DALAM LINTAS DEMOKRASI & PEMETAAN FILSAFAT HUKUM - mukhtarullah (Universitas Teknologi Surabaya, 2025)
The DPR together with the President still stipulates the revision of the KPK Law, namely Law No. 19 of 2019 concerning the KPK. Apart from that, it also sees that the IPK (Corruption Perception Index) in Indonesia continues to increase every year. Therefore, why is the author here interested in this theme because the KPK itself is being hotly discussed by the public, especially the TWK (National Interview Test) which makes the KPK even more chaotic. In a democratic society, the KPK is very important. However, in reality, the KPK is currently being oppressed, criminalization and other actions that in this case weaken the KPK continue to occur. So, is it true that in the era of President Jokowi like during the New Order or the Soeharto government. What is the strategy to foster an anti-corruption attitude in the younger generation in particular, considering that corruption cases in Indonesia itself are still ingrained. Then how is the case that occurred at the KPK if analyzed in the context of legal philosophy studies. The results of the study show that first, the criminalization of the KPK is seen in the utilitarianism school where the author uses the opinion of Jeremy Bentham (the founder of the utilitarianism school). Bentham stated that good law is a law that can fulfill the principle of maximizing happiness and minimizing pain in society. Second, regarding the revision of the KPK Law seen in the context of the legal realism school, which the author quotes from the opinion of Axel Hegerstrom (one of the Scandinavian legal realism figures). That the opinion conveyed by Hagerstrom is that the law must be based on empirical reality that is in accordance with the psychological feelings of each individual. Keywords: Corruption Eradication Commission; Polemic; KPK Law; Indonesia